Validation of the Six-item Female Sexual Function Index in Middle-Aged Brazilian Women - Mona Lúcia Dall'Agno; Charles Francisco Ferreira; Fernanda Vargas Ferreira; Faustino R. Pérez-López; Maria Celeste Osório Wender (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective To validate the six-item female sexual function index (FSFI-6) in middleaged Brazilian women. Methods Cross-sectional observational study, involving 737 (premenopausal n = 117, perimenopausal n = 249, postmenopausal n = 371) Brazilian sexually active women, aged between 40 and 55 years, not using hormonal contraceptive methods. The Brazilian FSFI-6 was developed from the translation and cultural adaptation of the Portuguese FSFI-6 version. The participants completed a general questionnaire, the FSFI-6, and the menopause rating scale (MRS). The validation was performed by AMOS 16.0 software (SPSS, Inc., Chicago, IL, USA) for a confirmatory factor analysis (CFA). The chi-square of degrees of freedom (χ2/df), the comparative fit index (CFI), the Tucker- Lewis index (TLI) and the root-mean-square error of approximation (RMSEA) were used as indices of goodness of fit. Cronbach α coefficient was used for internal consistency. Results The process of cultural adaptation has not altered the Brazilian FSFI-6, as compared with the original content. The CFA for the FSFI-6 score showed an acceptable fit (χ2/df = 3.434, CFI = 0.990, TLI = 0.980, RMSEA = 0.058, 90% confidence interval (90%CI) = 0.033-0.083, p ≤ 0.001) and a good reliability was established in FSFI-6 and MRS (Cronbach α = 0.840 and = 0.854, respectively). In addition, 53.5% of the sample had low sexual function. Conclusion The FSFI-6 was translated and adapted to the Brazilian culture and is a consistent and reliable tool for female sexual dysfunction screening in Brazilianmiddleaged women.